ChemInform Abstract: Catalytic Enantioselective Allenoate—Alkene [2 + 2] Cycloadditions. Issue 34 (August 2015) - Conner, Michael L.; Xu, Yao; Brown, M. Kevin
Abstract A new and highly enantioselective method for catalytic [2 + 2] cycloadditions between unactivated alkenes and allenoates is disclosed.